DETERMINAN IMBAL HASIL INVESTASI PERUSAHAAN ASURANSI SYARIAH INDONESIA - Rosilawati, Weny; Syarif, Ahmad Hazas; Pratama, Anggi (Universitas Wiralodra, 2025)
The Islamic insurance industry plays an important role in mobilizing public funds and supporting economic stability through effective investment management. This study aims to examine the influence of contribution income (premi), claim expenses, and operational expenses on investment yield in Islamic insurance companies in Indonesia during the period 2019-2023. The research method used is quantitative with secondary data obtained from annual financial report. The sample consists of 6 Islamic insurance companies with a total 30 data points selected using purposive sanpling. Data analysis was conducted multiple linear regression aided by SPSS version 26. The results show that contribution income (premi) has a significant negative effect on investment yield, while claim expanses and operational expanses have significant positive effects. These findings imply that management in Islamic insurance companies should optimize claim and operational expense management to improve investment performance and ensure company sustainability.